Propolis: a review of its anti-inflammatory and healing actions - A. F. N. Ramos; J. L. Miranda (Journal of Venomous Animals and Toxins including Tropical Diseases, 2007)
Tissue healing is an adaptive biological response by which the organism repairs damaged tissue. The initial stage of healing is represented by an acute inflammatory reaction, in which inflammatory cells migrate to damaged tissue and phagocyte debris. At a later stage, fibroblasts and endothelial cells proliferate and generate a scar. The occurrence of inflammatory processes and healing imperfections have been a concern for hundreds of years, especially for individuals with healing difficulties, such as diabetics and carriers of peripheral circulation deficiencies. A wide variety of natural products have been used as anti-inflammatory and healing agents, with propolis being a remarkable option. Propolis has been used in popular medicine for a very long time; however, it is not a drug intended for all diseases. Currently, the determination of quality standards of propolis-containing products is a major problem due to their varying pharmacological activities and chemical compositions. The aim of this review is to discuss the use of propolis with emphasis on its anti-inflammatory and healing properties.